Fodor's Florence, Tuscany & Umbria - Lombardi, Matthew (New York : Fodor's Travel Publications, 2009)
A travel guide to Florence, Tuscany, and Umbria that provides information on the region's historical sites, landmarks, popular attractions, activities, hotels, restaurants, and shops.
"Pullout map inside"--Cover.
Includes index.
Young Adult
Keywords: Florence (Italy) -- Guidebooks; Tuscany (Italy) -- Guidebooks; Umbria (Italy) -- Guidebooks; Florence (Italy) -- Guidebooks; Tuscany (Italy) -- Guidebooks; Umbria (Italy) -- Guidebooks